Decade of Legal Data: Digital Forensics in the Workplace - Safitri, Sifa' Ulya; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
Digital Forensic Insights in Workplace: A Decade of Legal Data" provides a valuable dataset for researchers interested in the intersection of digital forensics and workplace investigations. This comprehensive resource streamlines the research process by offering a decade's worth of legal insights, from 2002 to 2012. Through meticulous filtering by document type and subject matter (Law), the dataset ensures relevance and accuracy. Our analysis highlights the most active institutions, prolific authors, and dominant research areas, such as Computer Security and Computer Science. With the data, researchers can gain valuable insights into digital forensics' legal aspects within workplace settings, fostering further exploration and scholarly work. Highlight: This dataset simplifies research in digital forensics within workplace contexts. It covers a decade of legal insights, offering valuable information from 2002 to 2012. Researchers can explore active institutions, prolific authors, and key research areas for scholarly work. Keywords: Digital Forensics, Workplace Investigations, Legal Insights, Dataset, Research Streamlining